An analysis of urban residents’ efficiency in paying for water services delivered by municipalities: A case of Chinhoyi Town, Zimbabwe - Chimwanda, Peter; Nyamugure, Philimon; Mdlongwa, Precious (Asian Journal of Empirical Research, 2023)
Chinhoyi urban local authority is failing to deliver obligated services such as water provision to residents, citing unavailability of funds due to non-payment by the residents as the main cause. This research aims at establishing whether or not this deterioration in water provision is indeed due to non-payment by citizens. Ten households were randomly selected from each of the sixteen residential areas in Chinhoyi. Each of the households was given a questionnaire to complete and the responses were analysed using Limdep and SPSS. The efficiency of residents in paying for water services was estimated using the Stochastic Frontier method. The factors that were used in the model were either quantitative or ordinal-qualitative. A likert-scale with ratings 1 to 5 was used for the ordinal factors. Results show that residents are paying for the water services provided by the municipality, suggesting that the poor supply of water by the Chinhoyi municipality is not due to non-payment by citizens. These results imply that revenue being collected from residents is either not sufficient for the provision of water or has a part that is being directed elsewhere. It was also established that water quantity, amount charged, household income, opportunism and inability significantly affect the amount of revenue paid to the municipality by the residents. The effect of opportunism and inability was, however, negative. Implying that an increase in each of the two factors reduces both the amount that a household will pay and the efficiency of the individual household.